Obravnava bolečine v fizikalni in rehabilitacijski medicini v Sloveniji - Podbregar, Primož (Rehabilitacija (Ljubljana), 2021)
Background: The purpose of our research was to determine the extent and characteristics of pain in rehabilitation medicine. We were interested in determining how the burden of reduced abilities due to pain is perceived by PRM specialists, their pain assessment, following of different guidelines and the use of pharmacological, physical and minimally invasive therapies as well as self-assessment of own pain management competencies and how they assess the need for additional training for pain management. Methods: In cooperation with the Special Interest Scientific Committee for Pain and Disability within European Society for PRM, we compiled a questionnaire, which we translated and adapted for Slovenia. Through an online survey platform, we emailed the questionnaire to the members of the Slovenian Society for Physical and Rehabilitation Medicine. Results: Twenty-eight FRM specialists completed the survey. All 28 respondents agreed that pain affects the outcome of rehabilitation. Impact of pain on rehabilitation outcome was estimated with a median of 60 %. At least one of available guidelines is followed by the respondents with a median of 80 % of their cases. The most frequently used pharmacological therapies for the treatment of pain are NSAIDs and paracetamol, all respondents use physical modalities, and minimally invasive techniques are used by 57 % of the respondents. The majority (86 %) gave either the answer that they have "some competencies" or "good competencies", while no one answered "I have no competencies", and only 14 % think that they have »very good competencies«. Conclusion: To our knowledge this is the first attempt to define the extent of pain management problems and its impact in the rehabilitation setting in Slovenia. The results will be used for further research in this area and to design measures for better understanding, detection and management of pain in rehabilitation medicine.
Keywords: bolečina; obvladovanje bolečine; Pain; pain management; Physical and Rehabilitation Medicine; rehabilitacija; rehabilitation; samoocena; self-assessment; specialist fizikalne in rehabilitacijske medicine; specialist in physical and rehabilitation medicine